Russia’s Policy of «Soft Power» in the Gulf States at the Beginning of the XXI Century - N V Slobodian (Vestnik RUDN. International Relations, 2013)
Russia’s national interests in the Persian Gulf region are distinguished at the article. The main foreign policy tools to promote Russian national interests in the Gulf region are considered. There were studied the stages of formation and legislative consolidation of the national interests of Russia in the Middle East region, shows the importance of this region to strengthen national security of the Russian Federation. Identified and analysed policy elements of «soft power» of the Soviet Union in the region, and distinguished tools of expansion and strengthening of Russian presence in the Persian Gulf using educational diplomacy, economic cooperation and other components of the policy of «soft power».